2016
DOI: 10.1146/annurev-pathol-012615-044241
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Disease of Eosinophilic Esophagitis

Abstract: Eosinophilic esophagitis (EoE) is a recently recognized inflammatory disease of the esophagus with clinical symptoms derived from esophageal dysfunction. The etiology of EoE is now being elucidated, and food hypersensitivity is emerging as the central cornerstone of disease pathogenesis. Herein, we present a thorough picture of the current clinical, pathologic, and molecular understanding of the disease with a focus on disease mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
60
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 182 publications
(284 reference statements)
0
60
0
6
Order By: Relevance
“…12 La disminución de la desmogleína-1, del complejo de diferenciación epidérmica y la fi lagrina produce aumento en la permeabilidad tisular; el aumento de CCL-26 y periostina promueve el reclutamiento de eosinófi los, que activados se acumulan y generan toxicidad celular, liberando factor de crecimiento transformante β, el cual estimula la fi brosis del músculo liso, ocasionando trastornos en la motilidad. 12 La sintomatología de los DGIE es crónica, variable e inespecífi ca, lo que hace difícil su identificación, generando retrasos en el diagnóstico y llevando a alteración de la calidad de vida del paciente, su estado emocional y entorno social. 13,14,15,16 Econó-micamente genera altos costos al sistema de salud y a los pacientes, secundarios a las múltiples pruebas que se utilizan para la aproximación diagnóstica, el seguimiento estrecho que requieren y el tratamiento de las secuelas.…”
Section: Introductionunclassified
“…12 La disminución de la desmogleína-1, del complejo de diferenciación epidérmica y la fi lagrina produce aumento en la permeabilidad tisular; el aumento de CCL-26 y periostina promueve el reclutamiento de eosinófi los, que activados se acumulan y generan toxicidad celular, liberando factor de crecimiento transformante β, el cual estimula la fi brosis del músculo liso, ocasionando trastornos en la motilidad. 12 La sintomatología de los DGIE es crónica, variable e inespecífi ca, lo que hace difícil su identificación, generando retrasos en el diagnóstico y llevando a alteración de la calidad de vida del paciente, su estado emocional y entorno social. 13,14,15,16 Econó-micamente genera altos costos al sistema de salud y a los pacientes, secundarios a las múltiples pruebas que se utilizan para la aproximación diagnóstica, el seguimiento estrecho que requieren y el tratamiento de las secuelas.…”
Section: Introductionunclassified
“…Although eosinophils are normally found throughout the gastrointestinal tract, even in the absence of microbiota or an adaptive immune system, they are not normally present in the healthy esophagus . Although the exact mechanisms of eosinophil recruitment in EoE are poorly understood, transcriptional profiling studies of esophageal tissues from EoE subjects revealed marked induction of eotaxin‐3 (CCL26), an IL‐13‐induced eosinophil chemotactic factor that plays a key role in eosinophil chemotaxis and activation …”
Section: Introductionmentioning
confidence: 99%
“…Eosinophilic esophagitis (EoE) is a chronic inflammatory disorder characterized by allergic hypersensitivity to food and eosinophilic infiltration in the esophageal mucosa (6). EoE pathogenesis is driven by IL-13-mediated transcriptional responses of the esophageal epithelium (7,8), which are collectively improved by steroids (9).…”
Section: Introductionmentioning
confidence: 99%